The Phenomenon Of Bullying Among University Students (Journal of the College of Basic Education, 2026)
Bullying is considered a learned behavior influenced by the social environment in which an individual grows up. It poses a danger to everyone involved—whether victims, bullies, or even bystanders. It is essential to correct the common misconception that bullying is a natural phenomenon among children that disappears on its own without the need for intervention. In reality, all parties associated with bullying suffer from psychological and physical effects that may negatively impact their lives and social relationships. Therefore, early intervention and increased community awareness are crucial steps to curb the spread of this phenomenon. There is also an urgent need to teach students effective skills for positive interaction with others (El-Dessouky, 2016: 5).The current research aims to:Assessing the level of bullying among university students.Assessing the significance of differences in bullying behavior among university students based on gender (male-female).Assessing the significance of differences in bullying behavior among university students based on academic level (first, second, third, and fourth year).A study was conducted on a sample of 100 university students, equally divided between males and females (50 male and 50 female students). A random sampling method was used to ensure fair representation of the research population. The researcher developed a bullying behavior scale for university students, consisting of 15 items, each with five response options, based on the Social Learning Theory (Al-Qahtani, 2012, p. 3). The researcher extracted the psychometric properties of the scale, including face validity, construct validity indicators, and item-total correlations. Reliability was measured through the test-retest method, confirming that the scale accurately measures the intended variable. After applying the scale to the research sample, the data was processed, and statistical methods such as the one-sample t-test and the independent samples t-test were used. The results indicated that the level of bullying among the university student sample was low. Based on the results, the researcher presented a set of conclusions, recommendations, and suggestions for further studies.